ANALISA IMPLEMENTASI STANDAR OPERASI PROSEDUR (SOP) TERHADAP KINERJA PETUGAS UNIT PELAYANAN JASA PENUMPANG PESAWAT UDARA (PJP2U) DI BANDAR UDARA INTERNASIONAL SOEKARNO HATTA JAKARTA - Ariyono Setiawan; Kevin Eliezer; Kukuh Tri Prasetyo (Politeknik Penerbangan Surabaya, 2019)
Airport revenue is consist of two sides , namely from the aeronautical bussiness sides from the non-aeronautical bussiness side, income from the aeronautical bussiness side, among others ; PJP4U, PJP2U, Aviobridge surcharge, check-in counter, and from the non-aeronautical bussiness side, that is ; tenant rent, vehicle parking, concession, advertisement. This two sides is the source of airport revenue, this units are very important to manage the airport revenue so it can improve commercial side of the airport. The PJP2U unit handles issues regarding passenger service and one of them is the PSC (Passenger Service Charge) still use work methods that some use the system but some still use the manual methods, which is one of them by using a hard copy passenger manifest that causes tha stack of manifest papers in the PSC office. And of course this method is not efficient compared to using a system that is integrated with the Airlines. This research was carried out aat the Soekarno-Hatta International Airport in Jakarta, in April – June 2018 with PSC unit officers as a population.This study is purposed to determine whether using an integrated system can help and make the work of PSC unit officers more efficient, and as one of the conditions to get the title of Associate Expert (A.Md) in the Diploma III program of Air Tansportation Management, Aviation Polytechnic of Surabaya.The method of data collection in this study uses the method of direct observation in the field, questionnaries, interviews, and literature studies. And the data processing method that will be used is with the help of the Statistical Product and Service Solution (SPSS) program.